2014
DOI: 10.1016/j.apcbee.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Methanol Synthesis Catalyst Deactivation in a Spherical Bed Reactor: An Environmental Challenge

Abstract: Catalyst deactivation and its environmental consequences are believed to be an important issue seriously needed to be dealt with. In this study, a mathematical model of a spherical bed along with the catalyst deactivation in a long-term operation period for the methanol synthesis was investigated. The inside space of the two spheres reactor configuration was filled with the catalyst. The materials in the outer surface of the inner hemisphere were understudied. The equations solved at two dynamic and static lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The other way to prevent sintering is to use promoters/protectors or complex bi-or tri-metallic catalysts. It was identified that the sintering of copper in the Cu/ZnO/Al 2 O 3 catalysts is one of the deactivation mechanisms in methanol synthesis [244][245][246]. In situ XRD tests were conducted for Cu/ZnO/Al 2 O 3 catalyst in the temperature range from 110 • C to 640 • C in a reduction atmosphere.…”
Section: Study Of the Process Of The Deactivation Of Catalystsmentioning
confidence: 99%
“…The other way to prevent sintering is to use promoters/protectors or complex bi-or tri-metallic catalysts. It was identified that the sintering of copper in the Cu/ZnO/Al 2 O 3 catalysts is one of the deactivation mechanisms in methanol synthesis [244][245][246]. In situ XRD tests were conducted for Cu/ZnO/Al 2 O 3 catalyst in the temperature range from 110 • C to 640 • C in a reduction atmosphere.…”
Section: Study Of the Process Of The Deactivation Of Catalystsmentioning
confidence: 99%
“…Particularly, Sadeghi et al [29] proposed a mathematical model for a spherical catalytic reactor in which the long term catalyst deactivation was considered. They studied the catalyst deactivation and reactor performance as a function of different parameters in the reactor and reaction.…”
Section: -Continues Packed Bed Spherical Reactorsmentioning
confidence: 99%
“…Many investigations focus on modeling of catalytic methanol synthesis reactor [7,[11][12][13][14][15][16][17]. In summary, Elnashaie and Wagialla [18] studied methanol production by the fluidized-bed reactor.…”
Section: Introductionmentioning
confidence: 99%